Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1021/acs.jpcc.0c07408
|View full text |Cite
|
Sign up to set email alerts
|

Hole Polaron Transport in Bismuth Vanadate BiVO4from Hybrid Density Functional Theory

Abstract: We address here the chemical character and the mobility of hole polarons in BiVO 4 (BVO). Two distinct structures for hole polarons in BVO have been reported in the literature to date. "Standard" hybrid density functional theory (DFT) calculations have predicted hole polarons to be (BiO 8 ) dodecahedroncentered polarons, while Hubbard U-DFT (DFT + U) calculations have predicted single oxygen atom-centered polarons. Resolving these contrasting findings is critical to validate theory in materials research. We in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 57 publications
1
28
0
Order By: Relevance
“…[9,10] In recent years, theoretical and experimental investigations have demonstrated that the charge polaron formation during the charge migration in the lattice of metal oxide photoanodes is an essential factor to impede charge transport in bulk as the polaron formed by charge carrier interacted with surrounding atoms moves slowly enough. [11][12][13][14] To inhibit the polaron formation, researchers have made many attempts, such as heteroatom doping, oxygen vacancy control, etc. [15][16][17][18] However, the electron and hole polarons of the BiVO 4 are localized in VO 4 units and BiO 8 units, respectively, [15][16][17][18][19] these previous attempts by heteroatom doping (substituting V atom), oxygen vacancies control, etc., that are suggested to be efficient for alleviating bulk recombination might only promote the electron migration, while the hole transport is scarcely tackled.…”
mentioning
confidence: 99%
“…[9,10] In recent years, theoretical and experimental investigations have demonstrated that the charge polaron formation during the charge migration in the lattice of metal oxide photoanodes is an essential factor to impede charge transport in bulk as the polaron formed by charge carrier interacted with surrounding atoms moves slowly enough. [11][12][13][14] To inhibit the polaron formation, researchers have made many attempts, such as heteroatom doping, oxygen vacancy control, etc. [15][16][17][18] However, the electron and hole polarons of the BiVO 4 are localized in VO 4 units and BiO 8 units, respectively, [15][16][17][18][19] these previous attempts by heteroatom doping (substituting V atom), oxygen vacancies control, etc., that are suggested to be efficient for alleviating bulk recombination might only promote the electron migration, while the hole transport is scarcely tackled.…”
mentioning
confidence: 99%
“…[32] Usually, the parameters of hybrid functional can be selected by fitting it to match the band gap of a material in the experiment. From the study of doing polarons calculations in TiO 2 [33] and BiVO 4 [34] etc., we find in some cases, the commonly used hybrid functional, like PBE0 and HSE06 (α = 0.25), have already given a band gap in good consistent with the experimental velue, but the polaronic states cannot be achieved using these hybrid functionals. Here in cases of the Ta 2 O 5 , TaON, and Ta 3 N 5 , the band gap in experiment [35] is 3.9, 2.4, and 2.1 eV, respectively.…”
Section: Cystal Structure and Polaron Binding Energiesmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23] Of particular interest in the present work are polaron defects in transition metal and maingroup oxides, where the extent of defect delocalization is sensitive to the fraction of exact exchange. [18][19][20][21][22][23][24][25][26][27][28][29][30] We demonstrate that density-corrected (DC-)DFT can be used both to detect and to correct over-delocalization of polaron defects. DC-DFT is a simple procedure whereby a selfconsistent Hartree-Fock (HF) density (ρ HF ) is used to evaluate the XC energy via a single Roothaan step: E xc [ρ HF ].…”
mentioning
confidence: 96%